Reaction Norm of Embryo Growth Rate Dependent on Incubation Temperature in The Olive Ridley Sea Turtle, Lepidochelys Olivacea, from Pacific Central America - Alejandra Morales-Mérida Berta; M. Bustamante Dulce; Monsinjon Jonathan; Girondot Marc (Journal of Embryology, 2017)
Olive ridleys (Lepidochelys olivacea) and loggerheads (Caretta caretta) are two closely phylogenetically related sea turtles that nest in very different thermal habitat. Olive ridleys nest in pan-tropical beaches whereas loggerheads nest in more temperate beaches. In the context of climate change, the temperature in temperate beaches will increase much more than for tropical beach due to buffering effect of air humidity in the later. We have determined the thermal reaction norm for embryonic growth in both species using field records of incubation temperatures and incubation length from loggerheads in Western Mediterranean Sea or olive ridleys from Pacific coast of Guatemala. We show that the optimum temperature for the growth of embryos is lower for loggerheads than for olive ridleys. This makes loggerhead turtles particularly sensitive to increase of beach temperature as it is expected due to effect of global warming in temperature regions. Furthermore, olive ridleys are more resilient to increase of temperatures and should not suffer from sublethal incubation temperatures.
Keywords: Growth